1997
DOI: 10.1128/jcm.35.1.25-32.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic characterization of five subspecies of Mycobacterium kansasii

Abstract: Different molecular typing methods including restriction fragment length polymorphism (RFLP) analysis with the major polymorphic tandem repeat (MPTR) probe and the IS1652 probe, pulsed-field gel electrophoresis (PFGE), amplified fragment length polymorphism (AFLP) analysis, and PCR restriction analysis of the hsp-65 gene (PRA) were applied to clinical and water isolates of Mycobacterium kansasii. RFLP with the MPTR probe, PRA, PFGE, and AFLP analysis revealed five homogeneous clusters which appeared to be subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
52
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(62 citation statements)
references
References 32 publications
9
52
0
1
Order By: Relevance
“…Symptoms of M. kansasii infections often resemble tuberculosis caused by M. tuberculosis complex bacteria. The PGRS and MPTR sequences can be used to type M. kansasii isolates with the aid of RFLP typing on the basis of these repetitive elements as probes [97, 294–296]. IS 1652 RFLP is only suitable for a limited number of M. kansassii subspecies [296, 297].…”
Section: Typing Methods For Other Mycobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Symptoms of M. kansasii infections often resemble tuberculosis caused by M. tuberculosis complex bacteria. The PGRS and MPTR sequences can be used to type M. kansasii isolates with the aid of RFLP typing on the basis of these repetitive elements as probes [97, 294–296]. IS 1652 RFLP is only suitable for a limited number of M. kansassii subspecies [296, 297].…”
Section: Typing Methods For Other Mycobacteriamentioning
confidence: 99%
“…The PGRS and MPTR sequences can be used to type M. kansasii isolates with the aid of RFLP typing on the basis of these repetitive elements as probes [97, 294–296]. IS 1652 RFLP is only suitable for a limited number of M. kansassii subspecies [296, 297]. Other typing methods are, for example, 16S‐23S spacer region typing [298]; large restriction fragment analysis [299], amplified fragment length polymorphism analysis [296]; PFGE [296], and PCR restriction analysis of the hsp‐65 gene [300].…”
Section: Typing Methods For Other Mycobacteriamentioning
confidence: 99%
“…Picardeau et al [70] found identical PFGE patterns for M. kansasii isolates from three HIV-negative patients from a single family living in the same household as for a shower isolate recovered from their home. A M. avium sputum isolate from a non-AIDS patient yielded an identical PFGE pattern as an isolate from a water sample isolated at home [73].…”
Section: Repeated Exposurementioning
confidence: 96%
“…Molecular typing methods demonstrated that M. kansasii is a heterogeneous species with several distinct subtypes (Ross et al, 1992;Alcaide et al, 1997;Iinuma et al, 1997;Picardeau et al, 1997;Richter et al, 1999;Gaafar et al, 2003;Taillard et al, 2003). PCR and restriction enzyme analysis (PRA) of the hsp-65 gene has been widely applied to studies concerning M. kansasii genotypic characterization (Ross et al, 1992;Picardeau et al, 1997;Richter et al, 1999;Taillard et al, 2003;Chimara et al, 2004). To date, such investigations have suggested that M. kansasii of PRA type I is the most prevalent type from clinical isolates worldwide and is only rarely isolated from the environment (Tortoli, 2003).…”
Section: Introductionmentioning
confidence: 99%